Analysis of the Application of Labor Law on Economic Growth in Indonesia - Calvita Calvita (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The government's efforts to overcome the global economic crisis with its citizens, especially business people, are one of the main reasons to stabilize the economy, maintain financial balance, and avoid bankruptcy for most businesses. Causes termination of employment and termination of employment. The problem of this research is to clarify whether labor law can be projected as a normative based law, namely a philosophical based law based on legal certainty and justice as well as benefits for producers (goods or services). In compiling this journal, the author uses the method of writing prescriptive law. This method aims to use legal norms and conduct normative legal research from an internal perspective. Labor law helps maintain order in the employment relationship between workers and employers. To maintain order, we need a code of conduct in the form of legal ideals, normative law (legal certainty) based on justice and expediency. These three values underlie compliance with labor law and as a rule of law Indonesia upholds caste equality before the law. (Equality before the Law).